Step * 1 1 1 of Lemma lsum-split

.....subterm..... T:t
1:n
1. Type
2. List
3. {x:T| (x ∈ L)}  ⟶ 𝔹
4. {x:T| (x ∈ L)}  ⟶ ℤ
5. l_sum(map(f;L)) (l_sum(map(f;filter(P;L))) l_sum(map(f;filter(λx.(¬b(P x));L)))) ∈ ℤ
⊢ map(λx.f[x];L) map(f;L) ∈ (ℤ List)
BY
((Assert L ∈ {x:T| (x ∈ L)}  List BY Auto) THEN EqCDA THEN FunExt THEN Auto) }


Latex:


Latex:
.....subterm.....  T:t
1:n
1.  T  :  Type
2.  L  :  T  List
3.  P  :  \{x:T|  (x  \mmember{}  L)\}    {}\mrightarrow{}  \mBbbB{}
4.  f  :  \{x:T|  (x  \mmember{}  L)\}    {}\mrightarrow{}  \mBbbZ{}
5.  l\_sum(map(f;L))  =  (l\_sum(map(f;filter(P;L)))  +  l\_sum(map(f;filter(\mlambda{}x.(\mneg{}\msubb{}(P  x));L))))
\mvdash{}  map(\mlambda{}x.f[x];L)  =  map(f;L)


By


Latex:
((Assert  L  \mmember{}  \{x:T|  (x  \mmember{}  L)\}    List  BY  Auto)  THEN  EqCDA  THEN  FunExt  THEN  Auto)




Home Index